Pengaruh Jumlah Industri, Indeks Demokrasi, Pendidikan, dan Upah Terhadap Pengangguran di Indonesia - M. Chusni Tamimi (Fakultas Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of the number of industries, democracy index, average years of schooling, and provincial minimum wage on the unemployment rate in Indonesia. This research employs a quantitative approach using panel data from 34 provinces over the period 2015–2024, sourced from Statistics Indonesia, and analyzed using the Fixed Effect Model with robust standard errors. The results indicate that all independent variables simultaneously have a significant effect on unemployment. Partially, the number of industries has a negative and significant effect, implying that an increase in industrial activity can reduce unemployment through job creation. The democracy index shows a negative but insignificant effect, suggesting that improvements in institutional quality have not yet directly impacted labor absorption. Meanwhile, the average years of schooling has a positive and significant effect on unemployment, indicating a mismatch between educational outcomes and labor market demands. Provincial minimum wages have a negative and significant effect, showing that wage increases are associated with improvements in labor market conditions. These findings highlight that reducing unemployment depends not only on industrial expansion but also on the quality of human resources, institutional effectiveness, and appropriate wage policies.
Finalisasi Rudy k_ 4 Agustus 2026
Keywords: labor market; industrialization; institutional quality; education mismatch; structural transformation